Successful Implantation of a Leadless Pacemaker in a Patient With a Tricuspid Clip - Maria Terricabras, MD (Elsevier, 2021)
Leadless pacemakers have become an effective alternative to conventional transvenous pacemakers to prevent the risk of lead failure, pocket complications, and iatrogenic tricuspid regurgitation. The current transcatheter approach for tricuspid valve repair can limit the implantation of these devices, unless the procedure is performed with appropriate image guidance. We present the case of a patient with severe tricuspid regurgitation secondary to pacemaker lead impingement who, despite the implantation of a tricuspid clip, received a leadless pacemaker. The procedure was successfully guided by transthoracic echocardiography, an alternative to transesophageal or intracardiac echocardiography. Résumé: Les stimulateurs cardiaques sans électrodes sont devenus une solution de rechange efficace aux stimulateurs transveineux classiques pour prévenir le risque de défaillance des électrodes, les complications liées à la loge et la régurgitation tricuspidienne iatrogène. L'approche actuelle de réparation de la valve tricuspide par cathétérisme peut empêcher l'implantation de ces dispositifs, à moins que l'intervention ne soit réalisée avec un guidage par image approprié. Nous présentons le cas d'un patient ayant une régurgitation tricuspidienne grave consécutive à la compression des électrodes d'un stimulateur cardiaque qui, malgré l'implantation d'un clip tricuspide, a reçu un stimulateur cardiaque sans électrodes. L'intervention a été guidée avec succès au moyen d'une échocardiographie par voie transthoracique, une solution de rechange à l’échocardiographie transœsophagienne ou intracardiaque.